Propulsion aéronautique : études expérimentales de la combustion - Vincent-Randonnier, Axel (Comptes Rendus. Mécanique)
Apart from light aviation, the majority of aeronautical propulsion relies on the implementation of turbomachinery, whose energy and environmental performances are continuously improving. After recalling the principles and operational scope of this type of engine, as well as the issues encountered in the study of combustion, we will discuss the resources deployed at the National Office for Aerospace Studies and Research (ONERA) to support the development and optimization efforts of engine manufacturers. Recent tests conducted with a new hydrogen-powered injector concept have drastically reduced nitrogen oxide emissions compared to a kerosene-powered engine.